2020
DOI: 10.3389/fncel.2020.582872
|View full text |Cite
|
Sign up to set email alerts
|

Xenon Exerts Neuroprotective Effects on Kainic Acid-Induced Acute Generalized Seizures in Rats via Increased Autophagy

Abstract: Xenon has been shown to have neuroprotective effects and is clinically used as a favorable safe inhalation anesthetic. We previously confirmed the neuroprotective effects of xenon treatment in epileptic animals. However, the mechanism underlying these protective effects remains unclear. We aimed to assess the effects of xenon inhalation on autophagy in neuronal injury induced by acute generalized seizures. Kainic acid (KA) was injected into the lateral ventricle of male Sprague–Dawley rats to induce acute gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Our data were consistent with previous reports that neuron autophagy induced by hypoxic-ischemia contributes to acute brain injury [5,24], supporting the notion that inhibition of neuron autophagy protects from HIBD in neonatal rats. Given that aberrant autophagy has been thought to participate in the pathogenesis of human diseases, including neurodegenerative diseases, such as Parkinson’s disease and Alzheimer’s disease [16], infectious and autoimmune diseases and various types of cancers [25] the inhibition of autophagy by Xe suggests that Xe may be valuable for the treatment of these chronic diseases. However, our findings were different from another report that induction of neuron autophagy reduces brain damage [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data were consistent with previous reports that neuron autophagy induced by hypoxic-ischemia contributes to acute brain injury [5,24], supporting the notion that inhibition of neuron autophagy protects from HIBD in neonatal rats. Given that aberrant autophagy has been thought to participate in the pathogenesis of human diseases, including neurodegenerative diseases, such as Parkinson’s disease and Alzheimer’s disease [16], infectious and autoimmune diseases and various types of cancers [25] the inhibition of autophagy by Xe suggests that Xe may be valuable for the treatment of these chronic diseases. However, our findings were different from another report that induction of neuron autophagy reduces brain damage [8].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, Xe can act as an antagonist of N-methyl-D-aspartate (NMDA) receptor, inhibitor of apoptosis, inhibiting potassium channel and others [13][14][15]. A recent study reveals that inhaling 70% Xe for 60 min significantly reduces the severity of neuronal damage caused by epilepsy [16]. However, the effect of Xe on neuroprotection in infants remains controversial [17,18] and whether Xe can modulate aberrant neuron autophagy and protect from HIBD in neonates has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…a current study on xenon and argon using oxygen-glucose deprivation in a hippocampal slice model [10]). Surveying the current literature on neuroprotection by noble gases, more articles on xenon [13 ▪▪ ,15 ▪▪ ,18,21 ▪ ,22,23,25,26] compared with argon [16 ▪ ,17,19 ▪ ,20,24 ▪▪ ] were found and experimental studies dominated the recent output (only one clinical study evaluating xenon was found [15 ▪▪ ]).…”
Section: Neuroprotectionmentioning
confidence: 99%
“…A PubMed search [21 March 2021; search strategy: neuroprotection AND (argon OR xenon OR noble gas)] revealed 23 articles, of which 10 had to be excluded (reviews: n = 6 reviews; technical reports: n = 3, editorial: n = 1). Thus, the results of 10 current original articles on neuroprotection derived by argon and xenon application [13 ▪▪ ,15 ▪▪ ,16 ▪ ,17,18,19 ▪ ,20,21 ▪ ,22,23,24 ▪▪ ,25,26] are summarized and integrated…”
Section: Introductionmentioning
confidence: 99%
“…Xenon can inhibit synchronous neuronal firing ( Uchida et al, 2012 ) and reduce neuronal damage caused by hyperexcitability by regulating glutamate metabolism ( Lavaur et al, 2016a , b ). Our previous studies demonstrated that xenon can inhibit seizures, neuronal damage, and cognitive deficits in kainic acid-induced status epilepticus and hypoxia-induced seizures ( Zhang et al, 2019 ; Zhang M. et al, 2020 ; Zhu et al, 2020 ). Our previous findings and results of other studies suggest that xenon may exert anti-seizure and neuroprotective effects during epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%